Prediction of myocardial infarction in patients with transient ischaemic attack. (10th October 2014) - Vilanova, M. B.; Mauri‐Capdevila, G.; Sanahuja, J.; Quilez, A.; Piñol‐Ripoll, G.; Begué, R.; Gil, M. I.; Codina‐Barios, M. C.; Benabdelhak, I.; Purroy, F.
<x xml:space="preserve">Abstract</x> Background Determinants of risk of myocardial infarction (MI) after transient ischaemic attack (TIA) are not well defined. The aim of our study was to determine the risk and risk factors for MI after TIA. Methods We prospectively recruited patients within 24 h of transient ischaemic cerebrovascular events between October 2006 and January 2013. A total of 628 TIA patients were followed for six months or more. MI and stroke recurrence (SR) were recorded. The duration and typology of clinical symptoms, vascular risk factors and aetiological work‐ups were prospectively recorded and established prognostic scores (ABCD2, ABCD2I, ABCD3I, Essen Stroke Risk Score, California Risk Score and Stroke Prognosis Instrument) were calculated. Results Twenty‐eight (4.5%) MI and 68 (11.0%) recurrent strokes occurred during a median follow‐up period of 31.2 months (16.1–44.9). In Cox proportional hazards multivariate analyses, we identify previous coronary heart disease (CHD) (hazard ratio [HR] 5.65, 95% confidence interval [CI] 2.45–13.04, P < 0.001) and sex male (HR 2.72, 95% CI 1.02–7.30, P = 0.046) as independent predictors of MI. Discrimination for the prognostic scores only ranged from 0.60 to 0.71. The incidence of MI did not vary among the different aetiological subtypes. Positive diffusion weighted imaging (DWI) (7.5% vs 2.5%, P = 0.007), and ECG abnormalities (Q wave or ST‐T wave changes) (13.6% vs 3.6%, P = 0.001) were associated to MI. Conclusion According to our results, discrimination was poor for all previous risk prediction models evaluated. Variables such as previous CHD, male sex, DWI and ECG abnormalities should be considered in new prediction models.